Effects of different intermittent pneumatic compression stimuli on ankle dorsiflexion range of motion - Yanaoka, Takuma; Numata, Urara; Nagano, Kanna; Kurosaka, Shiho; Kawashima, Hiroki (Frontiers in Physiology, 2022)
Despite substantial evidence of the effectiveness of intermittent pneumatic compression (IPC) treatments for range of motion (ROM) improvement, little evidence is available regarding how different IPC stimuli affect ankle dorsiflexion (DF) ROM. This study aimed to investigate the effects of different IPC stimuli on the ankle DF ROM. Fourteen, university intermittent team sport male athletes (age: 21 ± 1 years, height: 1.74 ± 0.05 m, body mass: 70.9 ± 7.7 kg, body fat percentage: 14.2 ± 3.6%, body mass index: 23.5 ± 2.5 kg/m2; mean ± standard deviation) completed four experimental trials in a random order: 1) no compression with wearing IPC devices (SHAM), 2) the sequential compression at approximately 80 mmHg (SQUEE80), 3) the uniform compression at approximately 80 mmHg (BOOST80), and 4) the uniform compression at approximately 135 mmHg (BOOST135). For the experimental trials, the participants were initially at rest for 10 min and then assigned to either a 30-min SHAM, SQUEE80, BOOST80, or BOOST135. Participants rested for 20 min after IPC treatment. The Weight-Bearing Lunge Test (WBLT), popliteal artery blood flow, pressure-to-pain threshold (PPT), muscle hardness, heart rate variability, and perceived relaxation were measured before (Pre) and immediately after IPC treatment (Post-0) and 20 min after IPC treatment (Post-20), and the changes in all variables from Pre (Δ) were calculated. ΔWBLT performance, ΔPPT, and Δperceived relaxation in all IPC treatments were significantly higher than those in SHAM at Post-0 and Post-20 (p < 0.05). ΔWBLT performance correlated with ΔPPT (p < 0.05). ΔPopliteal artery blood flow in BOOST80 and BOOST135 was significantly higher than that in SHAM and SQUEE80 at Post-0 (p < 0.05). ΔMuscle hardness and Δheart rate variability did not differ significantly between trials. In conclusion, IPC treatments, irrespective of applied pressure and mode of compression, increased ankle DF ROM. This resulted from decreased pain sensitivity (i.e., increased PPT). In addition, high inflation pressure and frequency did not provide additional benefits in increasing ankle DF ROM.